2000
DOI: 10.1128/mcb.20.20.7419-7426.2000
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Expression in Embryonic Stem Cells and Hematopoietic Stem Cells

Abstract: (18,19,31). In particular, the lack of significant provirus transcription in ES cells and their differentiated descendants has hampered the use of retroviral vectors in transgenic experiments (5,12,32). Interestingly, this block in provirus expression is maintained upon differentiation of infected cells despite the fact that primary infection of cells after differentiation results in efficient expression (6,7,26).Transcriptional repression is thought to be mediated by both cis-acting de novo methylation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
206
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 41 publications
(45 reference statements)
7
206
0
Order By: Relevance
“…We demonstrated that eGFP detection in HVS-T cell lines transduced with HRSIN-CSGW represents vector transduction (and not pseudotransduction 16 or expression from nonintegrated vectors 17,18 ) since the percentage of eGFP þ cells remained stable for at least 48 days as shown in Figure 2. This also supports that gene silencing 19 is not occurring in lentiviral-transduced HVS-T cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We demonstrated that eGFP detection in HVS-T cell lines transduced with HRSIN-CSGW represents vector transduction (and not pseudotransduction 16 or expression from nonintegrated vectors 17,18 ) since the percentage of eGFP þ cells remained stable for at least 48 days as shown in Figure 2. This also supports that gene silencing 19 is not occurring in lentiviral-transduced HVS-T cells.…”
Section: Discussionsupporting
confidence: 81%
“…17,18 Additionally, the expression of the transgene by transduced cells can be blocked by gene silencing. 19 The expression of eGFP protein was determined on days 7, 28 and 48 after a single round of cell transduction on day one. Figure 2 shows that the high percentage of transduced cells …”
Section: Cell Transduction and Vector Titrationmentioning
confidence: 99%
“…39,40 This indicates significant differences in epigenetic transgene regulation between primitive embryonic and adult stem cells, or, in general, between pregastrulation and postgastrulation cells. 41 It will be interesting to determine whether the type of control regions present in the vector, which lacked any element known to affect chromatin modulation besides a strong retroviral enhancer/promoter, 26 contributed to the promising outcome after immunoselection. Previous studies in murine HSCs used vectors with different cis-acting elements.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this low-frequency variegated pattern of expression is unknown, but it may be related to cytogenetic instability and karyotypic variability of this cell line 12,13 and also possibly to the unusual genomic structure of the G72 gene, in particular its location within a genomic region enriched in Long Terminal Repeat Elements 6 which are prone to transcriptional silencing. 14 In addition to…”
Section: Mitochondrial Localization Of G72mentioning
confidence: 99%